Melioidosis presenting as orbital and parotid abscesses with intracranial extension - Abdul Rani, Mohammed Fauzi; Samad Cheung, Humairah; Mohd. Shah, Azarisman; Mahmood, Tahir (International Islamic University Malaysia, 2002)
We report a fatal case of melioidosis in a diabetic patient presenting with orbital and parotid abscesses associated with intracranial subdural empyema. The likelihood of infections due to Pseudomonas pseudomallei is increased in patients with reduced immune status in endemic regions of the world. The risk to travellers to South East Asia in this era of global travel is also emphasized.